Pengaruh Media Sosial dan Brand Image terhadap Keputusan Pembelian Jasa Titip (Studi Kasus Pada El Jastip) - Emanuel Roberto Karlos; Nunsio Handrian Meylano; Dimas Realino (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
The development of digital technology and social media has changed consumer behavior in making purchases. Social media has not only become a means of communication but also serves as am effective marketing platform to introduce products or services. One phenomenon that has emerged is the personal shopping service (jastip), where consumers use a third party to buy goods from certain locations.This study aims to: 1. What is the relationship between social media, brand image, and purchase decisions for personal shoppers? 2. Does social media influence purchase decisions for personal shoppers? 3. Does brand image influence purchase decisions for personal shoppers? 4. Do social media and brand image simultaneously influence purchase decisions for personal shoppers. The population of this study was 97 El Jastip consumers. Simple random sampling was used in this study. This study employed quantitative methods, with data collection techniques involving questionnaires distributed to 97 respondents. Data were analyzed using validity and reliability tests, descriptive analysis, classical assumption tests, multiple linear regression, F-tests, and t-tests using SPSS version 23.The results showed that all research instruments were valid and reliable. Partially, the Social Media variable has a positive and significant effect on Purchase Decisions, and the Brand Image variable also has a positive and significant effect on Purchase Decisions. Simultaneously, both independent variables also significantly influence Purchase Decisions at El Jastip Maumere. The coefficient of determination (R²) of 0.317 indicates that Social Media and Brand Image contribute 31.7% to Purchase Decisions, while the remaining 68.3% is influenced by other factors outside this study.